(untitled) (Journal of Partial Differential Equations, 2000)
In this paper, we discuss the limit behaviour of solutions for a class of equivalued surface boundary value problems for parabolic equations. When the equivalued surface boundary Γ^ε_1 shrinks to a fixed point on boundary Γ_1, only homogeneous Neumann boundary conditions or Neumann boundary conditions with Dirac function appear on Γ_1.